A population based case-control study of agricultural injuries in children. Issue 3 (September 1996) - Stueland, D. T.; Lee, B. C.; Nordstrom, D. L.; Layde, P. M.; Wittman, L. M.
Abstract : OBJECTIVES: To identify preventable risk factors related to agricultural injuries occurring to children on family farms. SETTING: A geographically defined central region of Wisconsin, USA with nearly 1800 family dairy farms. METHODS: A two year, population based incidence study of occupational injuries among farm residents was conducted. For cases, trained staff abstracted information on the nature, severity, and treatment of the injury from the patient's medical record. Staff also administered a telephone questionnaire to cases and controls, usually answered by parents. RESULTS: There were 60 cases of farm residents younger than 18 years who sought care for acute agriculture related injuries. Farms on which uninjured children lived served as controls (n = 102). Multivariate analyses of 16 different variables revealed three significantly related to injuries to children: hours worked per week (odds ratio (OR) = 1.05; 95% confidence interval (CI) = 1.01 to 1.08); presence of disabled safety device (OR = 2.64; 95% CI = 1.10 to 6.35); and feeding cows by grazing (OR = 0.22; 95% CI = 0.06 to 8.83). CONCLUSIONS: Interventions designed to reduce the risk of agricultural injuries to farm children should acknowledge the participation of children as productive workers on the farm. Although education has been the standard method for encouraging safe practices in farm work, additional approaches, such as limiting the number of hours a child works, avoiding the disabling of safety devices, and using specific methods of managing cows, should also be adopted to minimize injury risks to farm children.